2020
DOI: 10.1108/ijchm-05-2020-0461
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hotel green business practices on consumers’ loyalty intentions: an expanded multidimensional service model in the upscale segment

Abstract: Purpose This study aims to present and empirically examines an expanded service model that incorporates green hotel practices together with a multidimensional/higher-order measurement model of service quality, as well as perceived value and satisfaction, to examine the relationships among these variables and hotel consumers’ loyalty/behavioral intentions (BI). Design/methodology/approach The model was examined using partial least squares structural equation modeling (PLS-SEM) using data gathered in August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(112 citation statements)
references
References 68 publications
11
101
0
Order By: Relevance
“…Miththapala et al 2013 (Assaker, 2020). These research findings provide the background for the hypothesis, which proposes;…”
Section: Conceptualizationmentioning
confidence: 80%
See 2 more Smart Citations
“…Miththapala et al 2013 (Assaker, 2020). These research findings provide the background for the hypothesis, which proposes;…”
Section: Conceptualizationmentioning
confidence: 80%
“…González-Rodríguez et al (2020) found that some cognitive processes might affect customers' willingness to pay more for staying in hotels concerned about the environment. Based on a study in the UK and upscale European hotels, Assaker (2020) has stated that green practices and service quality influence revisiting intentions. When reviewing global literature, several factors contributing to tourists' behavioral intention in the hotel industry can be found.…”
Section: Advantages Of Implementing Green Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors also indicated that this relationship influences less consumer behavior. Assaker, G. [3] affirms that there is a relationship between the green image of hotels and behavioral intentions, precisely, the intentions for developing word of mouth communication strategies or repeated purchases. In this context, we propose the first research hypothesis: Hypothesis 1 (H1).…”
Section: The Green Imagementioning
confidence: 99%
“…Simultaneously, it does not prevent them from worrying about environmental sustainability, integrating different actions and strategies for improving the overall situation, and until it becomes a corporate value of these companies. Similarly, in recent years there has been a growing concern among consumers for environmental preservation and responsible consumption [3,4]. In this context, hotel consumers show a positive attitude towards green hotel practices, which motivates hotels to continue working to improve their environmental impact performance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%